Tonga : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
In Tonga, the fiscal position has strengthened but vulnerabilities remain. Directors have welcomed Tonga's recovery from the global crisis but noted remaining vulnerabilities and a high debt burden. With downside risks clouding the outlook, Directors have emphasized the importance of strengthening policy buffers and the foundation for faster and more inclusive growth. Directors have also encouraged the authorities to implement their fiscal plans within a medium-term framework and to improve further the quality of public spending to meet Tonga's development objectives.